Gaucher disease in Brazil: a comprehensive 16 year retrospective study on survival, cost, and treatment insights - Borin, Marcus Carvalho; Alvares-Teodoro, Juliana; Acurcio, Francisco Assis; Guerra, Augusto Afonso (Frontiers in Pharmacology, 2024)
Background: Gaucher's disease (GD), a lysosomal storage disorder, poses significant treatment challenges. This 23-year study assesses survival rates and treatment efficacy in Brazilian GD patients, integrating data from a 16-year cohort (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) and the TABNET/DATASUS medicines distribution data .Objective: To investigate the survival of GD patients in Brazil, identifying key risk factors and evaluating the impact of treatments funded by the Brazilian National Health System (SUS).Methodology: A 16-year retrospective cohort study was conducted using the National Database of SUS. Patients diagnosed with GD and treated with Enzyme Replacement Therapy (ERT) or Substrate Synthesis Inhibition (SSI) from 2000 to 2015 were included. Survival analysis was performed using Kaplan-Meier method and Cox proportional hazards model. The data from TABNET/DATASUS system from 1999 to 2022 was used to assess the trend in drug distribution beyond the main cohort.Results: The study included 1,234 patients. Survival rates at 5 and 10 years were 93.2% and 88.5%, respectively, with age and comorbidities like diabetes, cardiovascular diseases, and Parkinson's disease significantly affecting survival. Patients who received doses lower than DDD (n=880) demonstrated a survival probability of 91.8%. In contrast, those with doses equal to the DDD (n=15) showed a 100% survival probability, as no events were observed in this group. The greater than DDD group (n=339) exhibited a survival probability of 81%. A log-rank test indicated a borderline statistical significance (p=0.058) in the survival distributions among the different DDD adherence, with the lower dose group showing a favorable trend.This study provides insights into the survival rates and associated risk factors for GD patients in Brazil, contributing to the global understanding of GD and its management. While we acknowledge the inherent limitations of relying largely on electronic medical records and categorical codes, our findings underscore the need for early diagnosis, timely initiation of treatment, effective management of comorbidities, and personalized dosing strategies to improve patient outcomes. Future studies should aim to incorporate clinical verification of electronic data to further enhance the reliability and applicability of these findings.